Inorganic polymers from laterite using activation with phosphoric acid and alkaline sodium silicate solution: Mechanical and microstructural properties. (January 2015) - Lassinantti Gualtieri, Magdalena; Romagnoli, Marcello; Pollastri, Simone; Gualtieri, Alessandro F.
Abstract: Geopolymers from laterite, an iron-rich soil available in developing countries, have great potential as building materials. In this work, laterite from Togo (Africa) was used to prepare geopolymers using both phosphoric acid and alkaline sodium silicate solution. Microstructural properties were investigated by scanning electron microscopy, X-ray powder diffraction and mercury porosimetry, whereas thermal properties were evaluated by thermal analyses. The local environment of iron was studied by X-ray Absorption Spectroscopy (XANES region). The mechanical properties were determined. Modulus of Rupture and Young's modulus fell in the ranges 3.3–4.5 MPa and 12–33 GPa, respectively, rendering the materials good candidates for construction purposes. Heating above 900 °C results in weight-gain, presumably due to iron redox reactions. X-ray Absorption Spectroscopy data evidence changes in the chemical and structural environments of iron following thermal treatment of geopolymers. These changes indicate interaction between the geopolymer structure and iron during heating, possibly leading to redox properties. Highlights: Geopolymerization of laterite is promising for fabrication of building materials. Both phosphoric acid and alkaline sodium silicate solution can be used for activation. Thermally activated redox properties of the inorganic polymers were observed